Transform : how leading companies are winning with disruptive social media - Morace, Christopher; Leslie, Sara Gaviser (McGraw Hill-Ascent Audio, 2013)
Transform ... or Be Left Behind Create unprecedented business value with social technologies Chief Strategy Officer at Jive Software, Christopher Morace was one of the first people to arrive at the intersection of social technology and business strategy. He has overseen more than 800 deployments of social technology in major corporations. A true pioneer of what is arguably the most important development in business today, Morace knows better than anyone how social technology is changing the way businesses operate and how successful companies are leveraging it to their advantage. Now, in this groundbreaking guide, Morace reveals all his secrets. He walks you through best practices for developing a winning business strategy that places heavy focus on collaboration, open communication, and wide networks of connections--absolute necessities for success in business today. Morace outlines the strategic steps every leader must take in order to compete in today's constantly shifting business landscape: Learn about the newest social and related technologies (such as mobile, the cloud, and big data) and the capabilities they offer. Enact the behavioral changes within your company that will enable these capabilities to be incorporated into day-to-day operations. Determine your starting point, choose a platform, launch a social business solution, and measure your progress. Transform is packed with firsthand accounts of companies that have taken these very steps to drive positive change, increase profits, and experience measurable growth. Morace gives you an inside look at how Chubb Insurance, McAfee, EMC, T-Mobile, Bupa, SolarWinds, UBS, Alcatel-Lucent, Genentech, and others have applied his methods. He also offers valuable commentary from industry professionals such as Marc Andreessen and academics from Stanford's Graduate School of Business and Dartmouth's Tuck School of Business. Technology is advancing at an exponential pace, and it's changing the way the world does business. You can keep doing things the way you've done them. Or you can Transform. The right choice is obvious--and simpler to implement than you might think. PRAISE FOR TRANSFORM "The tools and frameworks that Chris Morace describes in Transform are vital for companies looking to win in today's competitive market."--Aaron Levie, Cofounder and CEO, Box "This is a must-read book for any customer seeking to improve how work gets done, the customer experience, and the innovation cycle." -- R "Ray" Wang, Principal Analyst and CEO, Constellation Research, Inc. "My advice is simple: read this book if you want to empower your people and improve your organization." -- Andrew McAfee, Principal Research Scientist, MIT's Center for Digital Business, author of Enterprise 2.0, and coauthor of Race Against the Machine "There's a revolution happening in corporations around the world. To succeed in this revolution, knowledge has to be shared. You need a social platform, one like Morace describes, that knows what you want to know, presents ideas to you, and enables you to connect to the right people." -- Debby Hopkins, Chief Innovation Officer, Citi "Morace captures the process and effort that it takes to provide disruptive technologies flawlessly. Stop reading this endorsement and go buy the book already! Don't waste time. The next disruption may be your own--if you don't listen to what Morace is telling you." -- Paul Greenberg, author of the bestselling CRM at the Speed of Light: Social CRM Strategies, Tools, and Techniques for Engaging Your Customers, and President, The 56 Group, LLC